2018
DOI: 10.3311/ppee.11841
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Planning of Electric Car Charging Station Based on Discrete Time Observations and MAP(2)/G/c Queue

Abstract: The modeling of electric car charging stations is essential for determining the required number of chargers in order to ensure the required service quality. In this paper we propose a new estimation method for the stochastic modeling of electric car charging stations, based on Markov arrival process (MAP).The input of the proposed model is empirical data for the arrival and service process of electric cars, given as histograms: the number of arriving cars during a fixed time slot (5 minutes in our case) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In this paper we have proposed an accurate study based on the observed data involving Markov Arrival Process method in discrete steps. Also, we have taken three moments that are used in probability distribution curve and then studied their correlation with regression along with the observations that are in discrete form and discrete time intervals [1][2][3][4]. Studying discrete time method is better than continuous time method has already been proven above work.…”
Section: Literature Surveymentioning
confidence: 99%
“…In this paper we have proposed an accurate study based on the observed data involving Markov Arrival Process method in discrete steps. Also, we have taken three moments that are used in probability distribution curve and then studied their correlation with regression along with the observations that are in discrete form and discrete time intervals [1][2][3][4]. Studying discrete time method is better than continuous time method has already been proven above work.…”
Section: Literature Surveymentioning
confidence: 99%
“…One of the competitive advantages of filling stations will be that they can provide fast charging for long-distance journeys while also ensuring the required service quality (waiting and charging times). The service can be provided cost-effectivly using optimization techniques developed by Farkas and Telek (2018).…”
Section: E-pumpmentioning
confidence: 99%
“…Additionally, long-range broadcast mediums can also be used as control channels (for example in case of a malicious intervention), because in their cases the it is even more difficult to identify the perpetrator, through these channels multiple receivers can be commanded at once, and they do not make it necessary for attackers to know the precise parameters of the car. The modern automobile can include many broadcast receivers for long-range signals: Global Positioning System (GPS) (Kis and Lantos, 2013), Satellite Radio, Digital Radio, Radio Data System (RDS) and Traffic Message Channel (TMC) where signals are transmitted as digital subcarriers on existing FM-bands (Farkas and Telek, 2018).…”
Section: Long Range Wireless Attacksmentioning
confidence: 99%